The Internalization Process of Revelation of the Hidayatullah Organization's Systematic Values in the Social Construction of Miniature Islamic Civilization - Irfan Yahya, M. Tahir Kasnawi, Suparman Abdullah, Hasbi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this research is to examine the process of internalizing systematic revelation values as the manhaj of the Hidayatullah mass organization in carrying out the micro social construction of Islamic civilization. This study employs a phenomenological approach and focuses on the Systematics of Revelation as a manhaj through which Hidayatullah comprehends, believes, and practices social constructs. This study investigates the awareness of reality, including actuality and the systematic interpretation of revelation as Hidayatullah's manhaj. This research theory is based on Peter L. Berger's viewpoint. Internalization of Systematic Revelation ideals in a conscious, structured, and systematic manner in order to successfully grow humans as Abdullah (servants of Allah) and caliphs (representatives of Allah SWT) on earth based on the guidance of Allah's revelation to establish Islamic civilisation. Pesantren serves as a microcosm of Islamic civilization, demonstrating faith in all facets of everyday life for all cadres, congregations, and students. In Hidayatullah, the process of internalizing systematic revelation values is quite dynamic. The method involves both non-formal and formal schooling. Non-formal education is more successful in shaping perceptions, knowledge, and ideas about the systematic values of revelation, allowing it to mould or develop character and morality. Non-formal education differs from the formal education system notion during the internalization phase.